Bacterial Cross-Contamination in a Veterinary Ophthalmology Setting - Gentile, Dominic; Allbaugh, Rachel A.; Adiguzel, Mehmet C.; Kenne, Danielle E.; Sahin, Orhan; Sebbag, Lionel (Frontiers in Veterinary Science, 2020)
The present study describes the prevalence of bacterial cross-contamination in a veterinary ophthalmology setting, a serious issue that can result in healthcare-associated (or nosocomial) infections among patients and staff. Retrospective (n=5 patients) and prospective (n=23 patients) studies evaluated bacterial isolates in companion animals presenting with ulcerative keratitis, sampling the patients’ cornea and surrounding examination room, including the environment (exam table, countertop, floor) and ophthalmic equipment (slit lamp, transilluminator, direct ophthalmoscope, indirect headset, tonometer). Results of bacterial culture and antibiotic susceptibility testing were recorded, and degree of genetic relatedness was evaluated in six pairs of isolates (cornea + environment or equipment) using pulse-field gel electrophoresis (PFGE). Overall contamination rate of ophthalmic equipment, environment, and examination rooms (equipment + environment) was 42.9% (15/35 samples), 23.7% (9/38 samples) and 32.9% (24/73 samples), respectively. Methicillin-resistant Staphylococcus pseudintermedius (MRSP), a multi-drug resistant (MDR) pathogen with zoonotic potential, was isolated in 8.2% (6/73) of samples. The patient’s cornea was likely the source of cross-contamination in 50% (3/6) of MRSP pairs as evaluated by PFGE; notably, two of the three similar bacterial strains did not have an exact match of their antibiotic susceptibility profiles, highlighting the importance of advanced diagnostics such as PFGE to assess cross-contamination in healthcare facilities. Future work could examine the contamination prevalence of specific equipment or the efficacy of cleaning protocols to mitigate cross-contamination in veterinary practice.